Use of the Da Vinci SP surgical system in robot-assisted nipple-sparing mastectomy: a single-center, retrospective study - Sae Byul Lee; Jisun Kim; Il Yong Chung; Hee Jeong Kim; Jong Won Lee; Byung Ho Son; Beom Seok Ko (Scientific Reports)
Abstract We investigated the safety and performance of the Da Vinci SP single-port robot (SP robot) in nipple-sparing mastectomy (NSM) with immediate reconstruction. Medical records of 60 women aged ≥ 19 years who had undergone SP robot-assisted unilateral or bilateral NSM with immediate reconstruction between October 2020 and August 2021 were retrospectively analyzed. Stage I (31, 47.1%) was the most common pathological tumor-node-metastasis stage, followed by stages II (22, 33.3%), 0 (7, 10.6%), and III (4, 6.0%). The median total duration of NSM performed by a breast surgeon and reconstruction performed by a plastic surgeon was 154.0 min (interquartile range [IQR], 130.5–206.0 min) and 133.0 min (IQR, 80.0–255.0 min), respectively. The median length of hospitalization was 5.5 days (IQR, 3.0–9.0 days). Conversion to robotic multiport or open surgery was not required in any case. The median duration to drain removal was 5.0 days (IQR, 4.0–6.0 days). Recurrence of cancer within 6 months was not observed in any patient. SP robot-assisted NSM with immediate reconstruction was performed successfully in all patients without conversion to open surgery or the incidence of significant perioperative complications, indicating its precision and ability to minimize the size of the surgical incision.